If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6xy + 6xy = 0 Combine like terms: -6xy + 6xy = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| X(2)=5(5) | | f(-2)=(4m-3)/(m-7) | | 2(x-5)=7-2x | | 3sinx-4cosx-2=0 | | .2(7-x)=4 | | 5-3x-(-4x+6)=-(8x+11)-(3x-10) | | 42.5/y=x | | 2=(3+x)+3(2) | | x^(-1/5)=(1/3) | | x^-1/5=1/3 | | 8x+41y+10=180 | | 2n/3=4 | | x-x+3x+x+30+28=40 | | 5h-7-3h=2(h-14) | | a^3-64= | | (2c+1)=(c-5) | | 4x^2+4y^2-16x+32y-20=0 | | (2c-1)=(c-5) | | 12y-18/2 | | 16x-3=68+13+4x | | 2x+4x+2x+1+5x-6=60 | | r/s=25 | | 9x+1=9(1)+2 | | (37b-8)-9(4b+4)=-2 | | 96.8639/883.3525= | | 1-0.4p=2 | | 3x-6=-7x-6 | | 1x+16+56=90 | | (7+y)(5y+3)= | | 11x+35+35=180 | | 3p-42=31 | | 1-0.4=2 |